2017
DOI: 10.1002/cctc.201700383
|View full text |Cite
|
Sign up to set email alerts
|

RuCl3 Supported on N‐Doped Graphene as a Reusable Catalyst for the One‐Step Glucose Oxidation to Succinic Acid

Abstract: Impregnation of RuCl3 on N‐doped graphenes results in the formation of well‐dispersed, small ruthenium oxyhydroxide nanoparticles supported on N‐doped graphene that may exhibit high selectivity (87 %) for the conversion of glucose into succinic acid under wet oxidation conditions (160 °C, 18 atm O2 pressure). Ruthenium loading and N‐atom distribution on graphene influence the catalytic activity, the best performing catalyst having 1 wt. % Ru loading on a graphene having a large population of graphenic N atoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Therefore, a step forward represented the development of ruthenium oxyhydroxide nanoparticles supported on N-doped graphene catalysts. They are able to convert glucose to SA (selectivity of 87%) in the absence of an excess of amine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a step forward represented the development of ruthenium oxyhydroxide nanoparticles supported on N-doped graphene catalysts. They are able to convert glucose to SA (selectivity of 87%) in the absence of an excess of amine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we shown that N-containing graphenes obtained either by simultaneous amination and reduction of graphene oxide or by pyrolysis of chitosan under inert atmosphere may act as metal-free catalysts for the selective WO of glucose to SA [ 16 ]. However, the process is less efficient compared to corresponding Ru-based graphene catalysts [ 14 ]: at 160 °C, under 18 atm O 2 and after 20 h the selectivities to SA were in the range of 60–68% at a complete glucose conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The only limitation associated with this method was the continuous addition of primary amine while using the catalyst; this problem was further investigated by Rizescu et al, [27] in 2017. They prepared the catalyst by impregnating RuCl 3 on Ndoped graphene, which eliminated the need for the addition of butylamine during glucose oxidation, as now the source of nitrogen atoms coordinating to Ru ions was switched from a molecular additive to an embedded part of the support.…”
Section: Catalysts For Oxidationmentioning
confidence: 99%
“…In particular, Ru IV was stabilized; therefore, mediating the reaction rate and formation of succinic acid. Furthermore, n ‐butylamine could be replaced with N‐doped graphene as a support for the Ru catalyst to provide even better selectivity to succinic acid …”
Section: Conversion Of Cellulose Into Dicarboxylic Acidsmentioning
confidence: 99%